Complete Genome Sequence of the Mycobacterium immunogenum Type Strain CCUG 47286 - Jaén-Luchoro, Daniel (Genome Announc, 2016)
Here, we report the complete genome sequence of Mycobacterium immunogenum type strain CCUG 47286, a nontuberculous mycobacterium. The whole genome has 5,573,781 bp and covers as many as 5,484 predicted genes. This genome contributes to the task of closing the still-existing gap of genomes of rapidly growing mycobacterial type strains.